MUDHARABAH FINANCING SUPERVISION OF ISLAMIC BANKING IN INDONESIA - Bagas Heradhyaksa; Ruzian Markom (Diponegoro Law Review, 2018)
The regulation in Indonesia states that the supervision of mudharabah financing is the right of Islamic bank. The Regulation of Indonesian Bank number 7/46/PBI/2005 section 6 subsection C and in The Circular Letter of Indonesian Bank number 10/14/Dpbs states that the supervision is done by reviewing and requesting evidence from customer's business result report without being given more detailed about the procedure of conducting mudharabah financing supervision. The purpose of this research is to analyze regulation that regarding the mudharabah financing supervision inIslamic banking. The methodology used in this research is empirical juridical method. We applied the method by comparing between the existing regulations with the reality that occurred in the field. This study found that a more detailed regulation regarding supervision of mudharabah financing was needed. This is so that the process of monitoring mudharabah financing has a strong legal basis and standard among Islamic bank. Moreover, the customer can also understand the steps that should be taken in the implementation of mudharabah financing supervision.